Electrocardiographic Abnormalities among Suspected Female Patients of Cardiovascular Diseases with Chest Pain - Haldar, Ganesh Chandra; Hoque, AKM Aminul; Majumder, Ripon Chandra; Uddin, Md Shahab; Alam, Md Khorshed (Eastern Medical College Journal, 2025)
Background: Cardiovascular disease (CVD) is the leading cause of global mortality for both genders. Electrocardiographic abnormalities play a key role in diagnosing CVD, particularly in patients experiencing chest pain. This study aimed to assess electrocardiographic abnormalities in suspected female patients of cardiovascular diseases with chest pain. Methods: This prospective observational study was conducted at the Department of Medicine, Eastern Medical College & Hospital, Cumilla, Bangladesh from January 2022 to June 2023. A total of 164 suspected female patients of cardiovascular diseases with chest pain were enrolled in this study as the study subjects. Purposive sampling was applied for sample selection and MS Office tools were used for data analysis. Results: Among the participants, major ECG (electrocardiography) abnormalities included the left bundle branch block (1.2%) and right bundle branch block (1.8%). Sinus bradycardia (12.2%) left anterior fascicular block (4.9%), and incomplete right bundle branch block (3.7%) constituted minor abnormalities. QRS axis deviations were noted in 4.9% and 1.2% of cases for left and right deviations, respectively. Chamber enlargement patterns revealed left ventricular hypertrophy in 3.7% and left atrial enlargement in 4.9% of cases. Brugada pattern and anterior early repolarization were found in 0.6% of cases each. Additionally, ST segment depression (5.5%), T wave inversion (6.7%), and Q wave (1.8%) were observed. Conclusion: In suspected female patients with chest pain and cardiovascular concerns, ECG proves to be an effective tool for detecting major abnormalities such as left and right bundle branch block as well as minor abnormalities like sinus bradycardia, left anterior fascicular block, and incomplete right bundle branch block. ECG serves as a cost-effective and less cumbersome alternative to more advanced diagnostic methods like echocardiography or angiography. Eastern Med Coll J. July 2025; 10 (1): 71-75